The Impact of Discount Framing on Purchase Intention with Brand Reputation as a Mediator: A Study on Shopee E-Commerce - Tarmizi, Putri; Roslina, Roslina; Husna, Nurul (LPPPIPublishing, 2024)
This study aims to examine the impact of discount framing on brand reputation and consumer purchase intention within the Shopee marketplace. Purchase intention, a crucial determinant of consumer decisions, is shaped by various individual factors and online platform experiences. Data were gathered via surveys and questionnaires from respondents with prior Shopee shopping experience. The analysis employed structural equation modeling and the Sobel test using SPSS software to explore the mediating role of brand reputation in the relationship between discount framing and purchase intention. The results reveal that discount framing significantly and positively influences both brand reputation and purchase intention. Furthermore, brand reputation was found to strengthen the link between discount framing and purchase intention, indicating that a positive brand reputation enhances the effectiveness of discount strategies in attracting consumers. These findings offer valuable insights for businesses to design more impactful marketing strategies, especially regarding discount management and brand reputation, ultimately contributing to improved customer satisfaction and business competitiveness.